2006
DOI: 10.1007/s12110-006-1009-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual coercion and forced in-pair copulation as sperm competition tactics in humans

Abstract: Rape of women by men might be generated either by a specialized rape adaptation or as a by-product of other psychological adaptations. Although increasing number of sexual partners is a proposed benefit of rape according to the "rape as an adaptation" and the "rape as a by-product" hypotheses, neither hypothesis addresses directly why some men rape their long-term partners, to whom they already have sexual access. In two studies we tested specific hypotheses derived from the general hypothesis that sexual coer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 52 publications
5
83
1
Order By: Relevance
“…If it is suspected that sexual infi delity occurred recently, men may engage in sexual coercion, thereby minimizing the risk of cuckoldry via sperm competition. Th is hypothesis is supported by research indicating that men are more likely to engage in sexual coercion when the perceived risk of cuckoldry is high (Goetz & Shackelford, 2006;Lalumière, Harris, Quinsey, & Rice, 2005;Th ornhill & Palmer, 2000;Wilson & Daly, 1992). Although these behaviors are clearly abhorrent, they do not appear to be arbitrary or merely a manifestation of men's desire for power and dominance.…”
Section: In the Name Of Lovementioning
confidence: 94%
“…If it is suspected that sexual infi delity occurred recently, men may engage in sexual coercion, thereby minimizing the risk of cuckoldry via sperm competition. Th is hypothesis is supported by research indicating that men are more likely to engage in sexual coercion when the perceived risk of cuckoldry is high (Goetz & Shackelford, 2006;Lalumière, Harris, Quinsey, & Rice, 2005;Th ornhill & Palmer, 2000;Wilson & Daly, 1992). Although these behaviors are clearly abhorrent, they do not appear to be arbitrary or merely a manifestation of men's desire for power and dominance.…”
Section: In the Name Of Lovementioning
confidence: 94%
“…Rape also occurs in non-marital intimate relationships. Goetz and Shackelford (2006) secured prevalence estimates of rape in intimate relationships from a sample of young men and from an independent sample of young women in a committed relationship for at least one year, but not necessarily married. Goetz and Shackelford documented that 7.3% of men admitted to raping their current partner at least once, and 9.1% of women reported that they had experienced at least one rape by their current partner.…”
Section: Sexual Violencementioning
confidence: 99%
“…It is biologically impossible for women to be cuckolded, so one would not expect women to possess sperm competition psychology that would generate sexually coercive behavior in response to a male partner's sexual infidelity. Goetz and Shackelford (2006) documented in two studies that a man's sexual coercion in the context of an intimate relationship is related positively to his partner's infidelities. According to men self-reports and women's partner-reports, men who used more sexual coercion in their relationship were mated to women who had been or were likely to be unfaithful, and these men also were likely to use more mate retention behaviors.…”
Section: Sexual Violencementioning
confidence: 99%
“…Following Goetz and Shackelford (2006), we operationalized sperm competition risk as men's perceptions of their partner's past infidelity and likelihood of future infidelity.…”
Section: Study 1: Men's Reportsmentioning
confidence: 99%